Insect-pathogen crosstalk and the cellular-molecular mechanisms of insect immunity: uncovering the underlying signaling pathways and immune regulatory function of non-coding RNAs - Mahanta, Deepak Kumar; Bhoi, Tanmaya Kumar; Komal, J.; Samal, Ipsita; Nikhil, R. M.; Paschapur, Amit Umesh; Singh, Gaurav; Kumar, P. V. Dinesh; Desai, H. R.; Ahmad, Mohammad Abbas; Singh, P. P.; Majhi, Prasanta Kumar; et al. (Frontiers in Immunology, 2023)
Multicellular organisms are constantly subjected to pathogens that might be harmful. Although insects lack an adaptive immune system, they possess highly effective anti-infective mechanisms. Bacterial phagocytosis and parasite encapsulation are some forms of cellular responses. Insects often defend themselves against infections through a humoral response. This phenomenon includes the secretion of antimicrobial peptides into the hemolymph. Specific receptors for detecting infection are required for the recognition of foreign pathogens such as the proteins that recognize glucans and peptidoglycans, together referred to as PGRPs and βGRPs. Activation of these receptors leads to the stimulation of signaling pathways which further activates the genes encoding for antimicrobial peptides. Some instances of such pathways are the JAK-STAT, Imd, and Toll. The host immune response that frequently accompanies infections has, however, been circumvented by diseases, which may have assisted insects evolve their own complicated immune systems. The role of ncRNAs in insect immunology has been discussed in several notable studies and reviews. This paper examines the most recent research on the immune regulatory function of ncRNAs during insect-pathogen crosstalk, including insect- and pathogen-encoded miRNAs and lncRNAs, and provides an overview of the important insect signaling pathways and effector mechanisms activated by diverse pathogen invaders.